Using Digital Sandbox Gaming to Improve Creativity Within Boys' Writing. Issue 2 (2nd April 2020) - Ellison, Mark; Drew, Christopher
ABSTRACT: There is a persistent "gender gap" in boys' literacy in the United Kingdom. This article reports on one technology-based intervention that may aid teachers in supporting boys to develop creativity within their writing. Boys from a Year 3 class used Minecraft – a sandbox computer game – to create virtual worlds that might help them to visualize the environments they write about. Through pre- and post-tests of writing samples and focus group interviews with students, the study finds positive potential in the technology-based intervention. Discussions with the students showed that the boys did not believe they were good writers and they were not aware of what was expected of them when writing. However, it was also clear from the discussions that the boys enjoyed engaging with an interactive stimulus, which aided their thinking and provided them with new creative ideas for their writing. The results from the written task were inconclusive, suggesting the need for further research.